Questioning the psycho-socio-cultural factors that contribute to the cases of suicide attempts: an investigation - (:unkn) unknown (ELSEVIER IRELAND LTD, 2000)
Suicide attempts can be described to include all actions tal;en by an individual to end their life as a result of acute desperation. In parallel with the changes in the make-up of human societies both globally and in this country in recent years, suicide attempts ale receiving attention in ever increasing proportions. The current study is aimed at investigating the psycho-socio-cultural factors that contribute to the known cases of suicide attempts. The study included 116 cases admitted to the Emergency Internal Medicine and Surgery Units of the University of Istanbul, Faculty of Medicine Hospital between 1 December 1998 and 31 May 1999. In only 47 cases, a 30-point questionnaire was used in several face-to-face interviews with the patients following the preparation of a clinical case study. In establishing the socio-demographic, socio-cultural and socio-economic attributes of each individual case, a range of contributing effective factors is questioned. Including the specific reasons for each suicide attempt, thc emotional state of the individual prior to the suicide attempt, the type of suicide action chosen and reasons for this selection, immediate family structure, personal psychiatric antecedent, substance abuse. The results of out investigations are compared with the existing literature in a multi-faceted discussion. (C) 2000 Elsevier Science Iceland Ltd. All rights reserved.
Keywords: suicide attempt; psycho-socio-cultural factors; RISK-FACTORS; UNEMPLOYMENT; ADOLESCENT; BEHAVIOR; ADULTS